Sierra Leone : : Diamond prospecting by the Consolidated African Selection Trust ; 1 - Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1933)
Colonial Office memoranda concerning diamond mining in Sierra Leone, the activities of the London-based company, the Consolidated African Selection Trust, and the British administration's share in the profits